Defects in tRNA Anticodon Loop 2′‐O‐Methylation Are Implicated in Nonsyndromic X‐Linked Intellectual Disability due to Mutations in FTSJ1. Issue 12 (10th September 2015) - Guy, Michael P.; Shaw, Marie; Weiner, Catherine L.; Hobson, Lynne; Stark, Zornitza; Rose, Katherine; Kalscheuer, Vera M.; Gecz, Jozef; Phizicky, Eric M.
Abstract : We report that cell lines from patients with non‐syndromic X‐linked intellectual disability (NSXLID) due to loss‐of‐function FTSJ1 mutations lack specific tRNA anticodon loop modifications, as also found in yeast trm7 mutants. We also reporta novel NSXLID‐associated FTSJ1 ‐p.A26P missense allele, which yields tRNA missing only one of the expected modifications, just asin the corresponding yeast mutant. Our work suggests thatthese tRNA modification defects cause FTSJ1 ‐associated NSXLID, and demonstrates high conservation between human FTSJ1 and yeast Trm7. ABSTRACT: tRNA modifications are crucial for efficient and accurate protein synthesis, and modification defects are frequently associated with disease. Yeast trm7Δ mutants grow poorly due to lack of 2′‐ O ‐methylated C32 (Cm32 ) and Gm34 on tRNA Phe, catalyzed by Trm7‐Trm732 and Trm7‐Trm734, respectively, which in turn results in loss of wybutosine at G37 . Mutations in human FTSJ1, the likely TRM7 homolog, cause nonsyndromic X‐linked intellectual disability (NSXLID), but the role of FTSJ1 in tRNA modification is unknown. Here, we report that tRNA Phe from two genetically independent cell lines of NSXLID patients with loss‐of‐function FTSJ1 mutations nearly completely lacks Cm32 and Gm34, and has reduced peroxywybutosine (o2yW37 ). Additionally, tRNA Phe from an NSXLID patient with a novel FTSJ1‐p.A26P missense allele specifically lacks Gm34, but has normal levels of Cm32 and o2yW37 . tRNA Phe from the corresponding Saccharomyces cerevisiae trm7‐A26P mutant also specifically lacks Gm34, and the reduced Gm34 is not due to weaker Trm734 binding. These results directly link defective 2'‐ O ‐methylation of the tRNA anticodon loop to FTSJ1 mutations, suggest that the modification defects cause NSXLID, and may implicate Gm34 of tRNA Phe as the critical modification. These results also underscore the widespread conservation of the circuitry for Trm7‐dependent anticodon loop modification of eukaryotic tRNA Phe .